2022
DOI: 10.1155/2022/1523287
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Non-Newtonian Characteristics of Water Flow in Micro-/Nanochannels and Tight Reservoirs

Abstract: The characteristic scale of pore flow in tight reservoirs is generally in the range of 0.1 μm to 1 μm, which shows the obvious micro- and nanoscale effect. The traditional oil and gas seepage theory cannot accurately describe the flow law of liquid in the micro- and nanopores. The determination of seepage characteristics is crucial to the development, layout, and prediction of tight oil. Therefore, a non-Newtonian fluid model is established to discuss the flow characteristics of confined liquid in the heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Qinfeng Di et al found that the velocity of the water flow on the surface of the nanoadsorption layer was no longer zero, and the water flow rate increased. The effect of reducing pressure and increasing injection was remarkable. ,, Hua and Di developed a calculation model of the microscopic interaction energy, and the results showed a hydrogen bond interaction between nanoparticles and the wall of reservoir microchannel, indicating that nanoparticles are absolutely dominant in the competitive adsorption process with water molecules. Gu et al established a mathematical model for the flow slip of the nanoparticle adsorbent layer and deduced the slip length formula.…”
Section: Nano-depressurization and Injection Mechanismmentioning
confidence: 99%
“…Qinfeng Di et al found that the velocity of the water flow on the surface of the nanoadsorption layer was no longer zero, and the water flow rate increased. The effect of reducing pressure and increasing injection was remarkable. ,, Hua and Di developed a calculation model of the microscopic interaction energy, and the results showed a hydrogen bond interaction between nanoparticles and the wall of reservoir microchannel, indicating that nanoparticles are absolutely dominant in the competitive adsorption process with water molecules. Gu et al established a mathematical model for the flow slip of the nanoparticle adsorbent layer and deduced the slip length formula.…”
Section: Nano-depressurization and Injection Mechanismmentioning
confidence: 99%